Kegiatan Edukasi Digital “Bangun Komunitas Kreatif Bareng Tiktok Affiliate” - Rohmiati Rohmiati; Wiwien Wirasati; Rifda Kamilah; Salma Fanisya (Yayasan Literasi Sains Indonesia, 2026)
The development of digital technology has opened up various creative economic opportunities through the use of social media, one of which is the TikTok Affiliate program. However, productive use of digital platforms remains a challenge for students due to limited understanding of digital marketing, creative content creation, and affiliate program mechanisms. This Community Service (PKM) activity aims to improve digital literacy, understanding of digital marketing strategies, and creative content creation skills through TikTok Affiliate training. The activity was conducted with 15 students from the Communication Studies Program at the Indonesian Social and Political Sciences Institute (IISIP Jakarta) using a participatory training method that included material delivery, interactive discussions, content creation practices, and evaluation through pre- and post-tests. The results showed improvements in all assessment indicators. The average participant score increased from 50 in the pre-test to 85 in the post-test. The highest increase occurred in the knowledge indicator regarding the TikTok Affiliate feature, with a score increase of 43 points, followed by improvements in promotional content creation, storytelling, and digital trend utilization. In addition to improving participants' knowledge and skills, this activity also increased their confidence in utilizing social media as a means to develop their personal branding and creative economic opportunities. This activity demonstrated that practice-based training is effective in improving students' digital competencies and broadening their understanding of utilizing digital technology as an economic opportunity in the era of digital transformation.